Evaluation of the impact of Japan International Cooperation Agency's Assistance on the research and development capability of the Philippine Rice Research Institute - Payumo, Jane G. (Technology Management Center, 2003)
This study presents the results of the evaluation of the impact of Japan International Cooperation Agency's (JICA) assistance on the research and development (R&D) capability of the Philippine Rice Research Institute (PhilRice). It likewise discusses the following : (1) results of the technology audit; (2) strengths and weaknesses of the PhilRice-JICA collaboration; and (3) areas requiring attention to enhance positive impacts for the improvement of future collaborative R&D with JICA and other local and international organizations. Fifty respondents, representing three levels of management (top-,senior-, junior-level management) at PhilRice participated in the study. A total of 63 areas of policy and management related to R&D performance and technological capacity were used to assess impact. The technology audit focused on determining the technologies transferred to PhilRice and their contribution to the PhilRice's technological competence and sophistication. This study proved that the 11-year support of JICA in enhancing the institutional capabilities of PhilRice, in terms of facility upgrade, equipment support, and human resource development, has resulted in positive impacts on PhilRice's R&D performance and technological capacity enhancing the Institute's competitive advantage as an R&D organization. Such impacts to PhilRice can be observed in the following : (1) improved project management; (2) improved R&D management; (3) higher research performance, technical expertise, and learning capacity; (4) better merits and rewards structure; (5) increased in the number and quality of reports, and R&D projects; (6) increased institutional linkages; and (7) higher technological capacity and competence. These positive impacts could be further enhanced through the following : (1) implementation of technology planning, technology audit, and post-mortem analysis of projects; (2) institutionalization of the use of new project management software systems; (3) provision of explicit funding to pursue intellectual property protection, knowledge management activities, improvement of information system and generation and management of databases; and (4) exert of effort to compile institutional project reports published internationally.